2022
DOI: 10.1101/2022.09.29.509673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Induced mineralization in Escherichia coli biofilms: the key role of bacterial alkaline phosphatase

Abstract: Biofilms appear when bacteria colonize a surface and synthesize and assemble extracellular matrix components. In addition to the organic matrix, some biofilms precipitate mineral particles such as calcium phosphate. While calcified biofilms induce diseases like periodontitis in physiological environments, they also inspire the engineering of living composites. Understanding mineralization mechanisms in biofilms will thus provide key knowledge for either inhibiting or promoting mineralization in these research … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Bacteria often reside in the form of biofilms where the cells are embedded in a secreted network composed of polysaccharides, proteins, and extracellular nucleic acids that form the extracellular matrix (ECM). 39,40 Indeed, it has been shown that biofilms precipitate CaCO 3 41−43 conferring them structural support and mechanical stability 44 and that biofilms precipitate calcium phosphates crystals 45 in situ, and when formed in catheters they provoke their blockage. 46 Bacteria have been traced in the urine of kidney stones patients, 47,48 and isolated bacteria and biofilms were observed in the nidus and surface of renal calculi.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria often reside in the form of biofilms where the cells are embedded in a secreted network composed of polysaccharides, proteins, and extracellular nucleic acids that form the extracellular matrix (ECM). 39,40 Indeed, it has been shown that biofilms precipitate CaCO 3 41−43 conferring them structural support and mechanical stability 44 and that biofilms precipitate calcium phosphates crystals 45 in situ, and when formed in catheters they provoke their blockage. 46 Bacteria have been traced in the urine of kidney stones patients, 47,48 and isolated bacteria and biofilms were observed in the nidus and surface of renal calculi.…”
Section: Introductionmentioning
confidence: 99%